Fuel Recovery from Thermal Processing of Post-consumer Footwear Waste - K. Y. Tippayawong (2018)
©, Copyright Association of Energy Engineers (AEE). Currently, almost 25 billion pairs of shoes are annually manufactured worldwide. Logically, a large amount of footwear waste is generated. Economically and environmentally acceptable disposal of the waste is needed. In the present work, fuel recovery from thermal processing of shoe waste is considered. Energetic content of shoe waste was estimated. Thermal degradation characteristics and distribution and yields of the products were analyzed. They were carried out using a macro scale, thermogravimetric analyzer and gas chromatography. It was found that the calorific value of the shoe waste was high (21 MJ/ kg). Analysis revealed that the pyrolysis of shoe waste at atmospheric pressure started around 100°C and finished at about 700°C. Three degradation temperature regions during pyrolysis of the shoe waste were recorded. Products of pyrolysing waste comprised solid residue (around 26%), liquid (around 34%) and gas fraction (around 40%). Product gases contained fractions of combustible components, i.e., H 2 , CH 4 and CO. Valuable materials, fuel and energy may be recovered from footwear waste.